Stakeholders' satisfaction with civil engineering graduates - Musyafa, Albani (Curtin University, 2009)
Engineering education is being viewed as a fundamental matter in modern industry because engineering education produces graduates that are very important to the continued development of industry. Because of its importance, the quality of the engineering education should be improved continuously. Basically, the quality of education can be divided into the quality of the process and the quality of the outcome. The process includes the quality of the teaching, learning and curriculum, and the quality of the outcome is the quality of the competencies possessed by graduates. While the quality of curriculum and learning have been discussed in many scientific reports, the quality of competence is rarely discussed. Therefore, a study on the quality of graduates’ competence will be useful to augment recent studies on the quality of engineering education.The objective of this study is to analyse data of graduate quality so that useful information is obtained to help engineering education providers put strategies in place to improve its quality. The information includes the models linking quality and satisfaction.Data for this study including competence of graduates, performance of graduates, satisfaction of stakeholders, and expectations of stakeholders were obtained by survey with the questionnaire sets developed based on established variables and indicators. The targeted respondents are industry personnel monitoring graduates in workplaces. For comparison, data from academicians and professionals also were collected. Because of the diverse nature of engineering disciplines, the survey is limited to Civil Engineering graduates completing their studies from universities in Australia in recent years.The collected data were analysed using statistical methods in levels of samples and population. The variables related to competencies have been ranked so that the weaknesses and strengths of the competencies can be understood. The variables related to the expectations of stakeholders are also ranked so that the competencies that should be prioritized in education are identified. The characteristics of stakeholders’ satisfaction is defined based on the performance of graduates. Reliable models linking graduates’ competence and the stakeholders’ satisfaction have been developed. These findings will be useful to improve the quality of engineering education especially in the division of Civil Engineering.